Amiodarone Protocol Provides Cost Effective Reduction in Postoperative Atrial Fibrillation - Mehaffey, J. Hunter (Ann Thorac Surg, 2018)
BACKGROUND: Postoperative Atrial Fibrillation (POAF) following cardiac surgery results in a significant increase in morbidity, mortality, and healthcare cost. Prophylactic amiodarone has been shown to reduce the incidence of POAF, however the cost-effectiveness of a protocol driven approach remains unknown. METHODS: All patients with a Society of Thoracic Surgeons (STS) risk score enrolled in a prophylactic amiodarone protocol (n=153) were propensity score matched 1:3 with patients prior to protocol implementation (n=3574). Using the matched cohort, multivariate logistic and linear regressions assessed the relative risks (POAF reduction and adverse medication effects) of amiodarone therapy and costs respectively. TreeAge cost-effectiveness software modeled effects of prophylactic amiodarone costs, complication rates and quality of life. RESULTS: Of patients eligible for the prophylactic amiodarone protocol, 94.3% (281/298) were enrolled. Prophylactic amiodarone significantly reduced the rate of POAF (25.7 vs 16.8%, p<0.0001). A total of 600 matched patients demonstrate no baseline differences in demographics, comorbidities, disease state, or operative factors with a significant reduction in POAF without an increase in other associated complications. Using these adjusted estimates, the prophylactic amiodarone protocol demonstrated a cost savings of $458 per patient. Sensitivity analysis confirmed the protocol is cost-effective for all protocol related POAF risk reductions below OR 0.726. CONCLUSIONS: Implementation of a prophylactic amiodarone protocol significantly reduced risk-adjusted rates of POAF with a cost savings of $458 per patient. This analysis demonstrates how rigorous quantitative analysis can evaluate the benefits of quality improvement projects.